The reflexive relationship between financial and social exclusion for the selected Central-Eastern European countries - Dorjnyambuu, Byambasuren (Public Finance Quarterly, 2023)
This study primarily examines how the risk factors that lead individuals to social exclusion, disadvantage, and deprivation contribute to financial exclusion and vice versa. This causal relationship for financial and social exclusion is formulated using the simultaneous equations model. Along with the causal relationship, this study identifies the leading personal and environmental determinants for both the probabilities of being unbanked and socially excluded. I use demographic, socioeconomic, and geographic information from the Life in Transition Survey III, conducted in 2016. The study found a reflexive causal relationship between financial and social exclusion in the selected Central-Eastern European countries. Namely, people at risk of social exclusion are more likely to be excluded from access to financial services. On the other hand, those at risk of financial exclusion are more likely to be socially excluded.